2020
DOI: 10.1021/acs.est.0c05450
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Radiocesium in Sediments in Fukushima Coastal Waters: Verification of Desorption Potential through Pore Water

Abstract: Concentrations of 137Cs in seawater, seabed sediment, and pore water collected from the area around Fukushima were investigated from 2015 to 2018, and the potential of coastal sediments to supply radiocesium to the bottom environment was evaluated. The 137Cs concentration in the pore water ranged from 33 to 1934 mBq L–1 and was 10–40 times higher than that in the overlying water (seawater overlying within 30 cm on the seabed). At most stations, the 137Cs concentrations in the overlying water and the pore water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Thus, in some lacustrine and marine sediment cores sampled shortly after the Chernobyl accident in areas affected by its radioactive fallout, it was observed that 134 Cs had penetrated into the sediment up to 10-20 cm depth (e.g., Petersen et al, 1990;Kramer et al, 1991;Robbins and Jasinski, 1995;Holby and Evans, 1996). Similar observations have been documented in some sedimentary systems affected by the Fukushima accident (e.g., Yoshimura et al, 2014;Otosaka et al, 2020). Diffusion models provided apparently satisfactory descriptions of the data, but in some cases, the required diffusion coefficients had unreliable values (Holby and Evans, 1996).…”
Section: ∂ ∂Zsupporting
confidence: 61%
“…Thus, in some lacustrine and marine sediment cores sampled shortly after the Chernobyl accident in areas affected by its radioactive fallout, it was observed that 134 Cs had penetrated into the sediment up to 10-20 cm depth (e.g., Petersen et al, 1990;Kramer et al, 1991;Robbins and Jasinski, 1995;Holby and Evans, 1996). Similar observations have been documented in some sedimentary systems affected by the Fukushima accident (e.g., Yoshimura et al, 2014;Otosaka et al, 2020). Diffusion models provided apparently satisfactory descriptions of the data, but in some cases, the required diffusion coefficients had unreliable values (Holby and Evans, 1996).…”
Section: ∂ ∂Zsupporting
confidence: 61%
“…However, 10 years after the accident, the 137 Cs supply from the deep layers might slow the 137 Cs concentration decrease in the surface sediment in this area. The slow decrease in 137 Cs concentrations at present is thought to be due to desorption of 137 Cs from sediment (Otosaka et al, 2020). Besides, higher 137 Cs concentrations in the surface layer of some cores (Nos.…”
Section: Discussionmentioning
confidence: 81%
“…The parameters for the sediment and 137 Cs are shown in Table 1. The desorption rate from seabed sediment (s -1 ), defined as the product of the kinetic coefficient for desorption from suspended matter (s -1 ) and the correction factor (-) in Kamidaira et al [15], was set to the same order as the value obtained by monitoring [19]. The other parameters are based on Kamidaira et al [15].…”
Section: Modelmentioning
confidence: 99%